Lipopolysaccharide‐primed heterotolerant dendritic cells suppress experimental autoimmune uveoretinitis by multiple mechanisms. Issue 3 (18th December 2016) - Klaska, Izabela P.; Muckersie, Elizabeth; Martin‐Granados, Cristina; Christofi, Maria; Forrester, John V.
Abstract : Dendritic cells are increasingly being evaluated as customized therapy for treatment of autoimmune diseases both in pre‐clinical studies as well as Phase 1 clinical trials. This manuscript discusses mechanisms underlying tolerogenic properties of dendritic cells using the model of experimental autoimmune uveoretinitis. We show that TLR ligation in the appropriate context can prime dendritic cells and enhance their tolerogenic suppressive effect through several mechanisms including inhibition of inflammasome activation. Summary: Exposure of bone‐marrow‐derived dendritic cells (BMDC) to high‐dose ultrapure lipopolysaccharide for 24 hr (LPS‐primed BMDC) enhances their potency in preventing inter‐photoreceptor retinoid binding protein: complete Freund's adjuvant‐induced experimental autoimmune uveoretinitis (EAU). LPS‐primed BMDC are refractory to further exposure to LPS (= endotoxin tolerance), evidenced here by decreased phosphorylation of TANK‐binding kinase 1, interferon regulatory factor 3 (IRF3), c‐Jun N‐terminal kinase and p38 mitogen‐activated protein kinase as well as impaired nuclear translocation of nuclear factor κ B (NF‐ κ B) and IRF3, resulting in reduced tumour necrosis factor‐ α (TNF‐ α ), interleukin‐6 (IL‐6), IL‐12 and interferon‐ β secretion. LPS‐primed BMDC also show reduced surface expression of Toll‐like receptor‐4 and up‐regulation of CD14, followed by increased apoptosis, mediated via nuclear factor of activated T cells (NFATc)‐2 signalling. LPS‐primed BMDC are not only homotolerant to LPS but are heterotolerant to alternative pathogen‐associated molecular pattern ligands, such as mycobacterial protein extract ( Mycobacterium tuberculosis ). Specifically, while M. tuberculosis protein extract induces secretion of IL‐1 β, TNF‐ α and IL‐6 in unprimed BMDC, LPS‐primed BMDC fail to secrete these cytokines in response to M. tuberculosis . We propose that LPS priming of BMDC, by exposure to high doses of LPS for 24 hr, stabilizes their tolerogenicity rather than promoting immunogenicity, and does so by multiple mechanisms, namely (i) generation of tolerogenic apoptotic BMDC through CD14:NFATc signalling; (ii) reduction of NF‐ κ B and IRF3 signalling and downstream pro‐inflammatory cytokine production; and (iii) blockade of inflammasome activation.